Ways of Spending Free Time by the Women Sentencend To Imprisonment as a Potential for Understanding the Meaning of Social Rehabilitation - Robert Opora (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
The purpose of the text is an attempt to present the ways of organizing the free time activities in isolation by adult women. The results were achieved by using the open - depth interviews with convicts in prisons. The excess of free time becomes a major problem, but it is also the opportunity for educational activities, not only correctional but also developing new competences. I am trying to show the difficulties with arranging of own area activities under duress by the prisoners. In the same activity I see an effort directed to becoming an responsible adult. The research proceedings took a character of the analysis of the meanings of the interview content of the respondents in such a way to create thematically homogenous condensation sense. The following types reflecting the meaning of the free time were distinguished: A) Work as a elementary descriptive dimension of the free time. B) Learning and completing the education as a form of spending the free time; C) Cultural - educational activities as a form of spending the free time; D) Games as a form of spending the free time; E) Sports activity as desirable and necessary result of competition; F) Free time as the time to contact family.